Research Trends in Technological Pedagogical Content Knowledge (TPACK) Research (2014-2024): A Scientometric Analysis - Krisnaresanti, Aldila; Ahman, Eeng; Istikomah, Navik; Suwatno, Suwatno; Budiman, Asep (FKIP Universitas Lampung, 2024)
Abstract: Research Trends in Technological Pedagogical Content Knowledge (TPACK) Research (2014-2024): A Scientometric Analysis. Objectives: Over the past 20 years, there has been significant progress in TPACK research. Rapid technological advances make research on TPACK very important. However, very few studies have examined references through the application of scientometric analysis. This study aims to identify current and future TPACK trends, subjects, publications, authors, keywords, and author collaboration networks in TPACK research. Methods: Scientometric analysis was carried out on data from the Scopus database, a total of 582 TPACK research publications published from 2014 to March 2024 with keyword Technological Pedagogical Content Knowledge. We also restrict content written in English and limit to final publication stage. This study analysis does not include books, newspaper articles, and book reviews. Data analysis used the R bibliometric packages biblioshiny and VOSviewer. Findings: Based on the analysis results, the keywords that appeared most frequently in publications were TPACK (194 articles). The Australian Journal of Educational Technology is the journal that publishes the most articles on the TPACK theme (24 articles) and also has the highest number of local citations. Chai is number one on the list of authors with the highest impact. Based on the co-occurrence network visualization and word cloud, the organizational support, especially school support, is not yet visible. China, Indonesia, Australia, and the USA are leaders in collaboratives about TPACK topic. Conclusion: This study provides in-depth information about keywords are most pertinent to research on TPACK; journals that hold significant influence, and authors demonstrate prolificacy in studies concerning TPACK; the current trends in TPACK research, and what priority areas warrant further investigation; and the collaborative networks among countries in TPACK research. Keywords: TPACK; scientometric; biblioshiny; research trends.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202426